Netflow Traffic Analyzer For worm detection- A Survey (International Journal of Engineering and Computer Science, 2014)
Due to easy access and requirement of the Internet make it more popular for research and information sharing. Because of this feature a malicious codes are also easily exchange. A worm (malicious codes) can disturb network and normal network operation. Internet worms are causes significant worldwide disruption, a huge number of infected hosts generate traffic, which will impact the performance of the internet. Therefore this is one of the areas where researchers are concentrating to find effective detection system, which will presence the worms and reduce the worm’s spread. This paper deals with a classified study of most important and commonly used methods for detecting internet worms using Netflow, which can help network managers to monitor suspect Internet worm’s activities by analyzing the source data from the router